2020
DOI: 10.1017/wet.2020.77
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of residual herbicides influenced by cover-crop residue for control ofAmaranthus palmeriandA. tuberculatusin soybean

Abstract: Field studies were conducted in 2018 and 2019 in Arkansas, Indiana, Illinois, Missouri, and Tennessee to determine if cover crop residue interfered with herbicides that provide residual control of Palmer amaranth and waterhemp in no−till soybean. The experiments were established in the fall with planting of cover crops (cereal rye plus hairy vetch). Herbicide treatments consisted of a nontreated or no residual, acetochlor, dimethenamid−P, flumioxazin, −pyroxasulfone + flumioxazin, pendimethalin, metribuzin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 37 publications
(48 reference statements)
2
10
0
Order By: Relevance
“…In addition to the weed suppression and ecological benefits from the all cover crops used. Our results supports previous research indicating that utilizing soil-residual herbicides along with cover crops improves control of palmer amaranth and/or waterhemp (Perkins et al, 2021). The use of cowpea as monoculture before pineapple plantation but also as intercrop is highly important as food source.…”
Section: Resultssupporting
confidence: 89%
“…In addition to the weed suppression and ecological benefits from the all cover crops used. Our results supports previous research indicating that utilizing soil-residual herbicides along with cover crops improves control of palmer amaranth and/or waterhemp (Perkins et al, 2021). The use of cowpea as monoculture before pineapple plantation but also as intercrop is highly important as food source.…”
Section: Resultssupporting
confidence: 89%
“…Pyroxasulfone/flumioxazin applied preemergence at 45 þ 35, 89 þ 70, 134 þ 106, and 268 þ 211 g ai ha -1 reduced MHR waterhemp density 88%, 98%, 100%, and 100%, respectively (Table 4); all interactions for MHR waterhemp density were additive (Table 4). These results are similar to other studies that reported large reductions in waterhemp biomass and density with pyroxasulfone and flumioxazin applied alone or in combination at comparable rates (Hedges et al 2018;Perkins et al 2020;Schryver et al 2017).…”
Section: Aboveground Mhr Waterhemp Biomass and Densitysupporting
confidence: 91%
“…Other methods that could also be used to reduce the vigour of A. palmeri include mulching and creating narrower row spaces between crops to increase competitive interactions with A. palmeri (Jha et al, 2010; Teasdale and Mohler, 2000; Yelverton and Coble, 1991). Research also highlights that a combination of an herbicide application programme followed by the planting of a cover crop in Winter can be used to control A. palmeri (Cahoon et al, 2015; Perkins et al, 2021). Considering this information, it would be of value for future research to investigate such combinations and identify which species are most successful at hindering the growth of A. palmeri without impacting subsequent crop development later in the growing season.…”
Section: Review Of the Research Into Control Techniquesmentioning
confidence: 99%
“…Previous reports in Georgia (USA) have estimated that the annual cost of control and loss of production caused by A. palmeri exceed US$10 million (Webster and Grey, 2015). To address these challenges, previous research and management of A. palmeri has been strongly focused on (i) competition and light‐limiting strategies (Perkins et al, 2021; Price et al, 2006; Teasdale and Mohler, 2000; Yelverton and Coble, 1991), (ii) herbicide application (Cahoon et al, 2015; Inman et al, 2016; Küpper et al, 2017, 2018; Perkins et al, 2021; Shyam et al, 2020; Torra et al, 2020), (iii) flood irrigation (Franca et al, 2020), (iv) manual removal and grazing management (Burrows and Tyrl, 2013; Leon and Wright, 2018; Sosnoskie and Culpepper, 2014), (v) prevention and early response protocols (Norsworthy et al, 2014) and (vi) tillage management (Aulakh et al, 2013; Chahal et al, 2020; Culpepper et al, 2010; Farmer, Bradley, et al, 2017; Farmer, Webb, et al, 2017; Franca, 2015; Jha and Norsworthy, 2009; Keeley et al, 1987). Notwithstanding the importance of these contributions to the global research and control attempts for A. palmeri , many have failed to completely control the species in the long‐term.…”
Section: Introductionmentioning
confidence: 99%